2014
DOI: 10.3856/vol42-issue1-fulltext-6
|View full text |Cite
|
Sign up to set email alerts
|

Efecto del fotoperiodo y la temperatura sobre la composicion bioquimica en reproductores silvestres de cabrilla sardinera, Mycteroperca rosacea (Streets, 1877)

Abstract: Efecto del fotoperiodo y la temperatura sobre la composición bioquímica en reproductores silvestres de cabrilla sardinera, RESUMEN. Se estimó el factor de condición (K), el índice gonadosomático (IGS), hepatosomático (IHS) y de grasa visceral (IGV), así como la composición bioquímica en diferentes tejidos de reproductores silvestres de cabrilla sardinera, Mycteroperca rosacea, para evaluarlos a lo largo de un ciclo reproductivo y ver la relación que presentan los cambios con respecto a la temperatura del agua … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…22201/ib.20078706e.2020.91.3273 Cabello (2004), Kanak and Tachihara (2008), Cabral-Solís et al (2010), andRuiz-Ramírez et al (2017). On the other hand, other authors (Aburto-Oropeza et al, 2008;Albieri, Araújo, & Ribeiro, 2010;Chandrasekhara & Krishnan, 2011;Estrada-Godínez et al, 2014;Volpato & Trajano, 2005) have pointed out that CF is not related to GSI in some tropical fish species because breeding fish do not stop feeding during the maturing and spawning stages. This is the opposite of what is observed in some temperate and cold water species such as salmonids, that stop feeding during the breeding period and use energy reserves from visceral fat and muscle for vital functions, which leads to a clear decrease in CF (Barnham & Baxter, 1998;Bureau et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22201/ib.20078706e.2020.91.3273 Cabello (2004), Kanak and Tachihara (2008), Cabral-Solís et al (2010), andRuiz-Ramírez et al (2017). On the other hand, other authors (Aburto-Oropeza et al, 2008;Albieri, Araújo, & Ribeiro, 2010;Chandrasekhara & Krishnan, 2011;Estrada-Godínez et al, 2014;Volpato & Trajano, 2005) have pointed out that CF is not related to GSI in some tropical fish species because breeding fish do not stop feeding during the maturing and spawning stages. This is the opposite of what is observed in some temperate and cold water species such as salmonids, that stop feeding during the breeding period and use energy reserves from visceral fat and muscle for vital functions, which leads to a clear decrease in CF (Barnham & Baxter, 1998;Bureau et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, fish reproduce when conditions are appropriate for the greater survival probability of larvae, avoiding periods of low food availability and, therefore, present slow growth (Chellappa et al, 2010). In areas close to the tropics, such as LPB, changes in temperature and photoperiod play an important role in the life cycle of fish, mainly in reproduction (Estrada-Godínez et al, 2014). Reyes-Salinas et al (2003) reported a seasonal trend in primary productivity (PP) in LPB, with 2 peaks per year, the first one in March (16 mg C m-3h-1) (when the photoperiod increases and heat starts to build up), and the second in October (5 mg C m -3 h -1 ) (when the photoperiod decreases and there is heat loss).…”
Section: Discussionmentioning
confidence: 99%
“…Se ha demostrado ampliamente que los cambios anuales en el fotoperíodo son los responsables del inicio de la maduración gonádica, activando el eje reproductivo endocrino de los peces con la consecuente utilización de recursos energéticos por parte de los tejidos reproductivos. En cambio, la temperatura es un factor de sincronización que indica si las condiciones son apropiadas para la reproducción e induce la maduración final de los gametos y el desove (Estrada-Godínez et al, 2014).…”
Section: Discussionunclassified
“…It has been widely demonstrated that annual changes in the photoperiod are responsible for the onset of gonadal maturation, activating the endocrine reproductive axis of fish with the consequent use of energy resources by the reproductive tissues. Instead, the temperature is a synchronizing factor that indicates whether the conditions are suitable for reproduction and induces the final maturation of the gametes and the spawning (Estrada-Godínez et al, 2014).…”
Section: Conclusionesmentioning
confidence: 99%
“…Foram usados os parâmetros de cor, luminosidade (L*) varia de 0 a 100 (preto a branco); parâmetro a* varia do verde (-) ao vermelho (+); parâmetro b* varia do azul (-) ao amarelo (+)(CIE, 1978). Para a determinação do índice hepatossomático foi utilizada a fórmula IHS (%) = (Wh/Wt) x 100 (em que Wh= peso médio do fígado em g, e Wt = peso médio total do peixe em g) e para o índice viscerossomático IVS (%) = (Wgv/Wt) x 100 (em que Wgt = peso das vísceras em g, e Wt = peso médio, total do peixe, em g)(ESTRADA-GODÍNEZ et al, 2014).Em três filés foram retirados 2g da musculatura (lado esquerdo) periodicamente nos tempos pré-determinados às 0, 3, 6, 24 e 48 horas pós-abate e armazenados em nitrogênio líquido para posterior avaliação da atividade basal das enzimas glutationa redutase (GR), catalase (CAT) e lactato desidrogenase (LDH). Para os ensaios enzimáticos, as amostras dos tecidos musculares foram homogeneizadas em solução resfriada de tampão fosfato 10mM, pH 7,5, utilizando-se um homogeneizador universal (1g de tecido 10mL -1 do tampão), de acordo comLins et al (2006).…”
unclassified